2022
DOI: 10.3389/fpsyg.2022.1004504
|View full text |Cite
|
Sign up to set email alerts
|

Moderate physical activity alters the estimation of time, but not space

Abstract: Moderate physical activity can influence cognitive functions and visual cortical activity. However, little is known about the effects of exercise on fundamental perceptual domains, such as spatial and temporal representation. Here we tackled this issue by testing the impact of physical activity on a temporal estimation task in a group of adult volunteers in three different conditions: (1) in a resting condition (baseline), (2) during moderate physical activity (cycling in place – PA), and (3) approximately 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 72 publications
2
10
3
Order By: Relevance
“…Another factor we can reasonably exclude is heart rate modulation. The results, confirming previous evidence (Petrizzo et al, 2022;Tonelli et al, 2022) demonstrated that the heart rate acceleration from the resting state to the maximal effort during running was not predictive of the effect magnitude, across all the experimental conditions. Heart rate level has long been considered a reliable indicator of arousal (Thayer, 1970), both of which might influence the speed of the internal clock.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Another factor we can reasonably exclude is heart rate modulation. The results, confirming previous evidence (Petrizzo et al, 2022;Tonelli et al, 2022) demonstrated that the heart rate acceleration from the resting state to the maximal effort during running was not predictive of the effect magnitude, across all the experimental conditions. Heart rate level has long been considered a reliable indicator of arousal (Thayer, 1970), both of which might influence the speed of the internal clock.…”
Section: Discussionsupporting
confidence: 88%
“…It is of interest to compare the present data also with the study by Tonelli et al (2022) investigating the effect of moderate cycling on visual time perception. The results, obtained with a reproduction paradigm, showed that while temporal distortions were qualitatively present across all the tested durations, they were statistically different from zero just in the milliseconds range (200 − 800 ms vs. 1.6 − 3.2 secs).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations